Eksperimen Pembakaran dalam Boiler untuk Evaluasi Kinerja dan Emisi Menggunakan Bahan Bakar Padat Kelapa Sawit - Muhtadin; Iqbal; Erdiwansyah; Muhammad Faisal; Mahyuddin; Yusrizal; Lindawati; Bahagia (Jurnal Serambi Engineering, 2024)
This research evaluates the performance and combustion emissions of boilers using solid palm oil waste fuel. Experiments were conducted by measuring operational parameters such as temperature, pressure and thermal efficiency at different load variations. Analysis of the combustion of three types of oil palm biomass shows that oil palm shells consistently reach peak temperatures faster and higher (800-900°C) than empty palm fruit bunches and palm fronds (600-700°C). This combustion pattern indicates that palm kernel shells are more suitable for rapid energy release applications. In contrast, empty palm fruit bunches and palm fronds are ideal for steady and sustained combustion. In addition, the emissions analysis identifies exhaust gas components including CO, CO₂, SO₂ and NOₓ. The results show that palm oil solid fuel has the potential to be an efficient alternative fuel with thermal efficiencies of up to 80%. However, there is still a need to consider exhaust emissions due to increased CO and NOₓ compared to conventional fossil fuels. This study provides insight into the use of palm oil waste for renewable energy, although further optimisation is required to reduce the environmental impact